Extremophiles: enzymes and industrial applications - Assis, Sandra Aparecida de; Alves, Daniela Silva dos Santos; Aires, Gardênia Araújo; Carvalho, Silvanir Figueiredo de (SITIENTIBUS série Ciências Biológicas, 2010)
Extremophiles are microorganisms adapted to live at high temperatures as thermal vents, low temperatures as in polar regions, high salt concentrations, on acidic and alkali pH values, or under high pressure as deep sea regions. The mesophilic enzymes have some restriction in relation to drastic conditions required for industrial processes, mainly due the low stability of their enzymes. The discovery of new extremophiles microorganisms as well as their products and enzymes had a great impact in the biotechnological field. These microorganisms produce biocatalyzers that operate under conditions in with mesophilic could not survive, allowing the development of additional industrial processes.